Performance Analysis of Grid-Connected Distributed Generation System Integrating a Hybrid Wind-PV Farm Using UPQC. (18th March 2022) - Lei, Tongfei; Riaz, Saleem; Zanib, Noor; Batool, Munira; Pan, Feng; Zhang, Shaoguo
Abstract : This work presents a distributed generation system (DG) that combines system of a wind turbine (WT) and photovoltaic (PV) using a unified power quality conditioner (UPQC). Along with providing active power (AP) to the utility grid, Wind-PV-UPQC improves PQ indicators, for example, voltage drops/surges, harmonics of grid voltages, and PF. Since Wind-PV-UPQC depends on dual compensation scheme, the parallel converter works as a sinusoidal voltage source, while the series converter works as a sinusoidal current source. In this way, a smooth transition from grid operation to island operation and vice versa can be achieved without load voltage transitions. In addition, in order to overcome the problems through abrupt solar radiation or wind speed variations, a faster power balance is achieved between the wind turbines, the PV array, and the grid, as FFCL pursue the production of the current references of series converter. Consequently, the dynamic reactions of the converter currents and the voltage of dc bus are enhanced. A comprehensive analysis of flow of the AP through the converters is done to ensure a proper understanding of how Wind-PV-UPQC works. Finally, the simulation results are shown to estimate the dynamic and static performance of Wind-PV-UPQC in conjunction with the power distribution system.